Notes on identity, distribution and typification of Merremia rajasthanensis (Convolvulaceae) an endemic species from India - Patil , S. B.; Patel , R. M.; Simões , A. R. G.; Shimpale, V. B. (Rheedea, 2025)
Merremia rajasthanensis Bhandari (Convolvulaceae) is a rare endemic species of Indian deserts (Western India). During ongoing revisionary studies of Indian Merremia, it was re-collected, photographed and described. The conservation assessment and notes on its identity are provided in the present paper. It is also lectotypified during the present communication.